Психолого-педагогічні умови формування професійної соціалізації студентів інженерних спеціальностей - Мовчан, Яна Олександрівна (Видавництво "ТК Меганом", 2015)
Підкреслено важливість формування професійної соціалізації студентів інженерних спеціальностей. Зроблено акцент на підготовці майбутніх інженерів та професійно-особистісних вимог до них. Запропоновано поняття професійної соціалізації студентів інженерних спеціальностей та її структурні компоненти з показниками. Розглянуто категорію психолого-педагогічні умови та їх вплив на формування професійної соціалізації майбутніх інженерів. Запропоновано дефініцію "психолого-педагогічні умови". Визначено психолого-педагогічні умови формування професійної соціалізації студентів інженерних спеціальностей. Розглянуто можливі способи реалізації визначених психолого-педагогічних умов. Запропоновано шляхи щодо розробки програми реалізації визначених психолого-педагогічних умов формування професійної соціалізації студентів інженерних спеціальностей.

It is highlighted the importance of professional socialization formation of students major in engineering. Attention is drawn to future engineers training and professional and personal demands for them. It is given the definition of professional socialization socialization of students major in engineering and its structure components with their attributes. It is dealt with "psychological and pedagogical conditions" category and its influence on professional socialization formation of future engineers. It is given the ‘psychological and pedagogical conditions’ definition. Psychological and pedagogical conditions formation of students major in engineering are proposed. It is dealt with possible methods of proposed psychological and pedagogical conditions realization. It is described in short the ways about developing the realization program of proposed psychological and pedagogical conditions of professional socialization formation of students major in engineering.
Psychological and pedagogical conditions of components formation of professional socialization of students major in engineering
Keywords: навчальний процес; вища технічна школа; освіта; психологія; мотивація; education; professional socialization; students; motivation; psychology; higher technical school